Internalisasi Nilai-Nilai Kepemimpinan Profetik di Lembaga Pendidikan Islam - Nasukah, Binti; Harsoyo, Roni; Winarti, Endah (Universitas Pesantren Tinggi Darul 'Ulum, 2020)
The purpose of writing articles is to discuss prophetic leadership, prophetic leadership values and internalization in Islamic educational institutions. Prophetic leadership is a leadership paradigm that refers to the concept of leadership of the Prophets. In contrast to conventional leadership theories whose ultimate goal is worldly pursuit, prophetic leadership is leadership in Islam that seeks to restore human nature as khalÄ«fah and â€˜abdu-llÄh. The idea of prophetic leadership is intended so that Muslims as the best people can realize the three ideals that become prophetic leadership values, namely humanization, liberation, and transcendence. The capitalist paradigm has trapped the subjects of Islamic educational institutions in materialist goals. Therefore, the process of internalizing prophetic leadership becomes a necessity in the effort to make Islamic educational institutions free from non-ethical behavior. These prophetic leadership values can be internalized either through the learning activities of a subject or subject or through managerial activities within an Islamic educational institution. Internalization requires a common paradigm by leaders, staff, and teachers. It takes an exemplary leader who has theological paradigm so that the process of internalizing prophetic leadership values can really be realized.